Karakteristik Malformasi Anorektal di RSUP Dr. Tadjuddin Chalid Makassar Tahun 2021-2024 - Rahman, Muhammad Fatur; Gani, Aziz Beru; Darma, Sidrah; Purnamasari, Reeny; Lestari, Nur Ayu (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the characteristics of anorectal malformation (AMR) patients treated at Dr. Tadjuddin Chalid General Hospital, Makassar City in the period 2021 to 2024. Using univariate analysis methods with medical record data, this study presents an overview of gender, initial age at surgery, anorectal malformation variants, and types of surgery performed on patients. The results showed that male patients dominated MAR cases with a proportion of 74.6%, while the other 25.4% were female. The initial age of surgery in most patients was ≤ 2 days (44.4%). The most common type of malformation found was the type without fistula (87.3%), followed by several types of rectovaginal, rectovesical, and other fistulas. Colostomy was the most common first surgical procedure performed, with 69.8% of patients undergoing the procedure. These findings are consistent with previous studies showing a male predominance in the incidence of MAR and a tendency to perform colostomy in the early stages of treatment. This study is expected to provide a clearer picture of the characteristics of MAR patients in Indonesia and the importance of early diagnosis and treatment to prevent complications.